2000
DOI: 10.1182/blood.v96.7.2317.h8002317_2317_2322
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the gene encoding neutrophil elastase in congenital and cyclic neutropenia

Abstract: Congenital neutropenia and cyclic neutropenia are disorders of neutrophil production predisposing patients to recurrent bacterial infections. Recently the locus for autosomal dominant cyclic neutropenia was mapped to chromosome 19p13.3, and this disease is now attributable to mutations of the gene encoding neutrophil elastase (the ELA2 gene). The authors hypothesized that congenital neutropenia is also due to mutations of neutrophil elastase. Patients with congenital neutropenia, cyclic neutropenia, or Shwachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
198
1
7

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(216 citation statements)
references
References 24 publications
10
198
1
7
Order By: Relevance
“…Heterozygous mutations in ELA2 are the most common genetic abnormality found in approx. 50-60% of CN patients, suggesting a dominant mechanism of action (Dale et al, 2000;Horwitz et al, 2007). However, some cases of CN with ELA2 mutations arise sporadically, consistent with its transmission as an autosomal dominant disorder (Horwitz et al, 2007).…”
Section: Pathophysiologymentioning
confidence: 98%
“…Heterozygous mutations in ELA2 are the most common genetic abnormality found in approx. 50-60% of CN patients, suggesting a dominant mechanism of action (Dale et al, 2000;Horwitz et al, 2007). However, some cases of CN with ELA2 mutations arise sporadically, consistent with its transmission as an autosomal dominant disorder (Horwitz et al, 2007).…”
Section: Pathophysiologymentioning
confidence: 98%
“…The majority of patients have an autosomal dominant trait due mainly to mutations in ELA2, the gene encoding neutrophil elastase. 70,71 The autosomal recessive form (Kostmann syndrome) accounts for about 30% of cases and is due mainly to mutations in the HAX1 gene. 72 In others, the underlying molecular cause is still unknown.…”
Section: Severe Congenital Neutropenia and Kostmann Syndromementioning
confidence: 99%
“…The total white cell count may be close to normal due to increased numbers of eosinophils and monocytes. 71,73 There can be a mild anaemia and thrombocytosis, 73 and there is an increased risk of transformation to MDS 74 or AML. 75 Rosenberg et al studied 374 patients with SCN and found that the cumulative incidence for MDS ⁄ AML was 21% after 10 years of granulocyte colony-stimulating factor (G-CSF) therapy and 36% after 12 years.…”
Section: Severe Congenital Neutropenia and Kostmann Syndromementioning
confidence: 99%
“…RNA was extracted from marrow light-density cell fractions. Mutational analysis of CSF3R and ELA2 was performed by sequencing of polymerase chain reaction (PCR)-amplified either genomic DNA or cDNA essentially as described (Ward et al, 1999b;Dale et al, 2000;Dror et al, 2000).…”
Section: Mutation Analysismentioning
confidence: 99%
“…After ELA2 was found to be associated with SCN (Dale et al, 2000), sequencing of genomic DNA from peripheral blood leucocytes from the previously reported SCN patient (Dror et al, 2000) was performed. This revealed a novel one base pair deletion at nucleotide (delG4981) that resulted in frame shift and premature termination of the mutant neutrophil elastase (A204fs210X).…”
Section: Identification Of a Constitutive Ela2 Mutationmentioning
confidence: 99%